Implicature Analysis on English Textbooks for Junior High School: A Comparison Between National and International English Textbooks - Ronanda Zahra; Theresia Arianti (Universitas Islam Sultan Agung, 2022)
Indonesian government provides both national schools and international schools with different English exposures and different language uses that are implemented in the textbooks. Considering the importance of understanding implicature for students, it needs to be investigated what type of textbook has sufficient resources of implicature for students’ learning. Nevertheless, there is a small number of previous researchers that consider comparing textbooks from different types of schools with different curricula in terms of conversational implicature. Therefore, this study aimed to identify the types and analyze the implied meaning of conversational implicature and flouting of Grice’s maxim that is used in When English Rings a Bell for Junior High School and Cambridge Global English for Lower Secondary textbooks, as well as to find the distinctions that are shown in both textbooks in terms of the implicature. This study employed a descriptive qualitative research method with a content analysis approach. This study found that there were 19 conversations from 241 pages collected from When English Rings a Bell and 17 conversations from 152 pages from Cambridge Global English for Lower Secondary which were categorized into GCI and PCI as well as the four maxims (Quality, quantity, relevance, and manner). Therefore, the percentage for the occurrence of conversational implicature and the flouting of the maxim is higher in the international textbook. In conclusion, as the whole comparison, the most noticeable distinction shown in both textbooks is in terms of the way both textbooks provide content of the learning material in the form of conversation. It is also shown the different level of language use in both textbooks that will affect the complexity of the implied meaning in the conversations where the international textbook provides conversations with clearer context and the implied meaning are way more complex.